Back Cover: Stable [48]‐, [50]‐, and [52]Dodecaphyrins(1.1.0.1.1.0.1.1.0.1.1.0): The Largest Hückel Aromatic Molecules (Chem. Eur. J. 23/2015). Issue 23 (1st June 2015) - Soya, Takanori; Kim, Woojae; Kim, Dongho; Osuka, Atsuhiro
<x xml:space="preserve">Abstract</x> Where do you get your graphite from? In their Full Paper on page 8435 ff., M. Pumera et al. find that the fundamental properties of natural graphites vary due to the different geological processes and environments at their points of origin. The origin can affect chemical reactivity and hence the properties of the derived graphene materials. The cover highlights the countries from which graphite samples used in the study were obtained (Czech Republic, Sri Lanka, and Zimbabwe), with the crosshairs pinpointing the locations of the graphite mines themselves. The background image shows a SEM image showing the typical lamellar structure of graphite.